PELAKSANAAN KESELAMATAN DAN KESEHATAN KERJA (K3) PADA PT. UBJ LOGISTIK - Barokah, Mutiara; Prihandono, Prihandono; Chalisyah, Elis; Soleha, Soleha (JURNAL LENTERA BISNIS, 2026)
This study was conducted to determine, find and describe the phenomenon or problems of Occupational Safety and Health (K3) at PT UBJ Logistik. This study is motivated by the importance of human resources in carrying out work. K3 is an effort to create a safe and healthy work environment for  workers, with the aim  of preventing work accidents, occupational diseases, and increasing work productivity. The purpose of this study is to determine the obstacles in the implementation of K3, to find solutions and overcome obstacles in the implementation of K3. This writing method uses qualitative descriptive, namely presenting a description of the problem or a certain condition without any special treatment of the object being studied. Data collection techniques are carried out using observation, interview and documentation techniques. Based on the results of this study, it can be concluded that the implementation of K3 carried out by PT UBJ Logistik is not good enough in implementing K3, because the K3 regulations applied by the company are not strict enough so that employees pay less attention to the importance of K3.